Glucose utilization and anti-oxidative mechanisms of the aqueous hunteria umbellata seed extract in alloxan-induced diabetic rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: In South-west Nigeria, water decoctions of Hunteria umbellata seeds are highly valued by traditional healers in the local management of diabetes mellitus, obesity and hyperlipidemia. Previous studies hypothesized one of the antihyperglycemic mechanisms of the aqueous seed extract of Hunteria umbellata (HU) to be mediated probably via increased peripheral glucose utilization. The present study, therefore, was designed at evaluating the peripheral glucose utilization and anti-oxidative mechanisms of 50 mg/kg, 100 mg/kg and 200 mg/kg of HU in alloxan-induced diabetic rats in Groups IV-VI rats as well as in the control groups (Groups I-III). Experimental type 1 DM was induced in male Wistar rats through intraperitoneal injection of 150 mg/kg of alloxan monohydrate in cold 0.9% normal saline after which the diabetic rats were orally treated with 50-200 mg/kg of HU for 14 days. Effects of HU on the rat body weight, percentage body weight changes and fasting blood glucose (FBG) were determined on days 1 and 15 of the experiment. Also, on day 15 of the experiment, HU effect on serum insulin, liver enzyme markers, proteins, albumin, triglyceride, total cholesterol and lactate dehydrogenase as well as on hepatic tissue oxidative stress markers, liver glycogen and glucose-6-phosphatase were determined after sacrificing the rats under diethyl ether anesthesia. Results showed that oral treatments with 50-200 mg/kg of HU caused significant (p